The Pengaruh Sektor Ekonomi Terhadap Pendapatan Asli Daerah (PAD) di Kabupaten Dairi - Monika Karolina Sianturi; Ahmad Albar Tanjung (Journal of Business and Economics Research (JBE), 2020)
The source of acceptance of each region is required to have the advantage of the economic sector to improve the welfare of the community. The economic sector is an indicator that entering into the business field contained in the PDRB shows the amount of production that has been created through each sector of the economy in a given year. Therefore, this study aims to determine the effect of the leading economic sector on the own-source revenue (PAD) of Dairi Regency from 2015 to 2019. The type of data used in this study is secondary data in the form of PDRB data in the economic sector of Dairi Regency which is found in the BPS of Dairi Regency. The analytical method used is Location Quetiont and Shift Share. The results of this study indicate that Dairi Regency has one leading sector out of seventeen existing economic sectors, namely the construction sector. The construction sector can be developed properly, of course, has a significant effect on increasing own-source revenue.